Saving for retirement intention, context, and behavior - Clark, Gordon L.; Strauss, Kendra 1975-; Knox, Janelle Kallie 1983- (Oxford University Press, 2012)
As individuals assume greater responsibility for retirement saving, the book analyses how people save and make financial decisions, taking into account the behavioural revolution and the effect of society and context. It shows an integrated approach to individual financial decision-making is necessary to address the apparent planning shortfall